ROS-Mediated Inhibition of S-nitrosoglutathione Reductase Contributes to the Activation of Anti-oxidative Mechanisms - Kovacs, Izabella; Holzmeister, Christian; Wirtz, Markus; Geerlof, Arie; Fröhlich, Thomas; Römling, Gaby; Kuruthukulangarakoola, Gitto T.; Linster, Eric; Hell, Rüdiger; Arnold, Georg J.; Durner, Jörg; Lindermayr, Christian (Frontiers in Plant Science, 2016)
Nitric oxide (NO) has emerged as a signaling molecule in plants being involved in diverse physiological processes like germination, root growth, stomata closing and response to biotic and abiotic stress. S-nitrosoglutathione (GSNO) as a biological NO donor has a very important function in NO signaling since it can transfer its NO moiety to other proteins (trans-nitrosylation). Such trans-nitrosylation reactions are equilibrium reactions and depend on GSNO level. The breakdown of GSNO and thus the level of S-nitrosylated proteins are regulated by GSNO-reductase (GSNOR). In this way, this enzyme controls S-nitrosothiol levels and regulates NO signaling. Here we report that Arabidopsis thaliana GSNOR activity is reversibly inhibited by H2O2 in-vitro and by paraquat-induced oxidative stress in-vivo. Light scattering analyses of reduced and oxidized recombinant GSNOR demonstrated that GSNOR proteins form dimers under both reducing and oxidizing conditions. Moreover, mass spectrometric analyses revealed that H2O2-treatment increased the amount of oxidative modifications on Zn2+-coordinating Cys47 and Cys177. Inhibition of GSNOR results in enhanced levels of S-nitrosothiols followed by accumulation of glutathione. Moreover, transcript levels of redox-regulated genes and activities of glutathione-dependent enzymes are increased in gsnor-ko plants, which may contribute to the enhanced resistance against oxidative stress. In sum, our results demonstrate that ROS-dependent inhibition of GSNOR is playing an important role in activation of anti-oxidative mechanisms to damping oxidative damage and imply a direct crosstalk between ROS- and NO-signaling.